Signaling diversity of mu- and delta- opioid receptor ligands: Re-evaluating the benefits of β-arrestin/G protein signaling bias - Graciela Pineyro (11414285) (2021)
Opioid analgesics are elective for treating moderate to severe pain but their use is restricted by severe side effects. Signaling bias has been proposed as a viable means for improving this situation. To exploit this opportunity, continuous efforts are devoted to understand how ligand-specific modulations of receptor functions could mediate the different in vivo effects of opioids. Advances in the field have led to the development of biased agonists based on hypotheses that allocated desired and undesired effects to specific signaling pathways. However, the prevalent hypothesis associating β-arrestin to opioid side effects was recently challenged and multiple of the newly developed biased drugs may not display the superior side effects profile that was sought. Moreover, biased agonism at opioid receptors is now known to be time- and cell-dependent, which adds a new layer of complexity for bias estimation. Here, we first review the signaling mechanisms underlying desired and undesired effects of opioids. We then describe biased agonism at opioid receptors and discuss the different perspectives that support the desired and undesired effects of opioids in view of exploiting biased signaling for therapeutic purposes. Finally, we explore how signaling kinetics and cellular background can influence the magnitude and directionality of bias at those receptors. Other Information Published in: Cellular Signalling License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.cellsig.2020.109906